In vitro repair of a defective EGFP transcript and translation into a functional protein. Issue 28 (17th June 2016) - Balke, Darko; Becker, Aileen; Müller, Sabine
Abstract : Twin ribozymes mediate the exchange of a short patch of RNA against an exogenous oligonucleotide within a suitable RNA substrate. Abstract : Twin ribozymes mediate the exchange of a short patch of RNA against an exogenous oligonucleotide within a suitable RNA substrate. Thus, twin ribozymes are promising tools for RNA repair, i.e. for the treatment of genetic disorders at the mRNA level. A number of twin ribozyme-mediated RNA fragment exchange reactions have been successfully demonstrated using short model substrates. Herein we show for the first time a twin ribozyme-mediated in vitro repair of a full-length transcript and translation into a functional protein. The system is based on the repair of a designed mutant EGFP mRNA containing the four-base deletion ΔACTC (190–193). Upon twin ribozyme-mediated replacement of a patch of 15 nucleotides with an externally added repair oligonucleotide (19 mer) the wild type sequence of the EGFP transcript could be restored with 32% yield. This is the first time that such a high twin ribozyme-mediated repair yield, so far observed only for short model substrates, has been obtained for a full-length mRNA. Translation of the repaired EGFP -ΔACTC mRNA produces functional EGFP, as detected by the restored fluorescence.